2021
DOI: 10.1155/2021/4586319
|View full text |Cite
|
Sign up to set email alerts
|

LINC00467, Driven by Copy Number Amplification and DNA Demethylation, Is Associated with Oxidative Lipid Metabolism and Immune Infiltration in Breast Cancer

Abstract: Breast cancer (BRCA) is a malignant tumor with a high incidence and poor prognosis in females. However, its pathogenesis remains unclear. In this study, based on bioinformatic analysis, we found that LINC00467 was highly expressed in BRCA and was associated with tumor metastasis and poor prognosis. The genomic and epigenetic analysis showed that LINC00467 may also be regulated by copy number amplification (CNA), chromatin openness, and DNA methylation. In vitro experiments showed that it could promote the prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…Moreover, LINC00467 could enhance expression of LIN28B through directly interacting with it [6]. Another in silico study in breast cancer has shown possible role of LINC00467 in the regulation of peroxisomal lipid metabolism and immune response through targeting miRNAs [7].…”
Section: Sponging Effects Of Linc00467mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, LINC00467 could enhance expression of LIN28B through directly interacting with it [6]. Another in silico study in breast cancer has shown possible role of LINC00467 in the regulation of peroxisomal lipid metabolism and immune response through targeting miRNAs [7].…”
Section: Sponging Effects Of Linc00467mentioning
confidence: 99%
“…Genomic and epigenetic analyses have shown the impact of copy number amplification, chromatin configuration, and methylation status of DNA on expression of this lncRNA. Copy number amplification and up-regulation of LINC00467 has been associated with the lower levels CD8 + and CD4 + T cells infiltrations [7]. LINC00467 level has also been reported to be elevated in colorectal cancer tissues compared with normal colon mucosal counterparts.…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression level of LINC00467 in BC tissues and cells is obviously upregulated compared with paired adjacent tissues and normal breast epithelial cells. Functionally, several research revealed that silencing LINC00467 could suppress BC cell proliferation, migration and invasion [42,43]. Mechanically, LINC00467 down-regulated miR-138-5p and protein level of lin-28 homolog B (LIN28B) via a direct interaction to serve as a potential target [43].…”
Section: Breast Cancermentioning
confidence: 99%
“…Mechanically, LINC00467 down-regulated miR-138-5p and protein level of lin-28 homolog B (LIN28B) via a direct interaction to serve as a potential target [43]. In addition, Bo et al [42]. explored more mechanisms that high expression of LINC00467 driven by DNA methylation is associated with the protein TGF-β2 expression and LINC00467 correlated with the infiltration of CD4 + and CD8 + T cells suggests that LINC00467 was likely to inhibit anti-tumor immunity.…”
Section: Breast Cancermentioning
confidence: 99%